The adaptive evolution of polar fishes: Structure, function and molecular phylogeny of hemoglobin - Verde, Cinzia; Di Prisco, Guido (2006)
P(論文) emperature affects all molecular processes and is the major determinant of habitat suitability. Whilst there is an increasing understanding of evolutionary adaptation to temperature in some processes, several key questions often remain open about the structure-function relationships associated with protein thermal adaptation. Proteins, such as hemoglobin, are highly sensitive to temperature and therefore, their structural and functional properties mirror the thermal conditions encountered by species during their evolutionary histories. The most stable thermal environments are aquatic; research on polar fishes has provided important insights into the details of thermal adaptation. In polar fishes, the evolution of hemoglobin includes adaptations with implications at the biochemical, physiological and structural levels. Although both are cold, the Northern and Southern polar oceans have very different oceanographic features. In comparison with Antarctic fish of the suborder Notothenioidei, Arctic fish are characterised by higher biodiversity and hemoglobin multiplicity. Within the study of the molecular bases of cold adaptation in fish inhabiting the polar habitats, and taking advantage of the information available on hemoglobin structure and function, the evolutionary history of the α and β globins of Arctic and Antarctic fish hemoglobins has been analysed, under the assumption of the molecular-clock hypothesis. departmental bulletin paper